Transtornos do humor em enfermaria de clínica médica e validação de escala de medida (HAD) de ansiedade e depressão Mood disorders among medical in-patients: a validation study of the hospital anxiety and depression scale (HAD) - Neury J. Botega; Márcia R. Bio; Maria Adriana Zomignani; Celso Garcia Jr; Walter A. B. Pereira (Universidade de São Paulo, 1995)
Para estimar a prevalência de transtornos do humor, foram utilizadas a entrevista estruturada, "Clinical Interview Schedule" (CIS-R), e a escala "Hospital Anxiety and Depression" (HAD) em 78 pacientes internados em uma enfermaria geral de adultos (43 homens e 35 mulheres, média de idade = 43,2 anos). Foi encontrada prevalência instantânea de 39% de transtornos do humor. Dezesseis (20,5%) pacientes preencheram critérios para ansiedade, a maioria dos casos sendo de gravidade leve. Vinte e seis (33%) casos de depressão foram detectados, 7 dos quais de gravidade moderada. Observou-se uma combinação de sintomas de preocupação, depressão, ansiedade e insônia. A HAD mostrou-se de fácil compreensão pelos pacientes. As subescalas de ansiedade e de depressão tiveram consistência interna de 0,68 e 0,77, respectivamente. A correlação dos itens com as respectivas subescalas sugere que essas possuem validades convergentes, não discriminantes. Com ponto de corte 8/9, a sensibilidade e a especificidade foram 93,7% e 72,6%, para ansiedade, e 84,6% e 90,3%, para depressão. Na prática clínica, a utilização da HAD poderia auxiliar na detecção de casos de transtornos do humor que necessitam de tratamento. The revised Clinical Interview Schedule (CIS-R) and the Hospital Anxiety and Depression (HAD) Scale were used to estimate the prevalence of mood disorders among 78 consecutive admissions to a general medical ward in a university general hospital in Brazil (43 males and 35 females; mean age = 43.2yr). Interviewers also completed a 5-point symptom severity scales for anxiety and depression. The definition of cases of anxiety [and depression] was based on two criteria: a. score > 2 on the CIS-R section of anxiety [> 4 on the CIS-R sections of depression and depressive ideas]; and b. score > 2 on the clinical severity scale for anxiety [score > 2 on the clinical severity scale for depression]. A 39% prevalence rate of affective disorders was found. Sixteen (20.5%) patients met criteria for anxiety, most of the disorders being of mild severity. Twenty-sic patients (33%) were depressed, 7 of them in a moderate degree. The HAD was easily understood by the patients. Anxiety and depression subscales had internal consistency of 0.68 and 0.77, respectively. At a cut-off point of 8/9 sensibility and specificity were 93.7% and 72.6% for anxiety, and 84.6% and 90.3% for depression. HAD items correlated positively with the respective subscales. To a lesser degree, they also correlated with the alternative subscale. Our findings confirm the high prevalence of mood disorders among medical in-patients. In clinical practice, the HAD may have a useful role in detecting those patients requiring further psychological care.